Experience with Fully Covered Self-Expandable Metal Stents for Esophageal Leakage in Children - Lange, Bettina; Demirakca, Süha; Kähler, Georg; Weiß, Christel; Wessel, Lucas; Kubiak, Rainer (Klinische Pädiatrie, 2020)
Background There is a lack of experience with fully covered self-expandable metal stents (SEMSs) for the treatment of esophageal leakage particularly in infants and neonates.Methods Eight patients (5M, 3F) with a median age of 17 months (range, 1–135 months) who underwent treatment with SEMSs for an anastomotic leakage or perforation of the esophagus were recruited to this retrospective study. Four children were born premature. In six patients the stents were placed primarily as an emergency procedure.Results Median duration of individual stent placement was 42 days (range, 13–72 days). Six out of eight patients (75%) were treated with one stent only. In three preterm infants who had their stents inserted within the first month relative weight gain was 17% compared with 2% in five patients who were treated later in life (p=0.0986). In four cases (50%) distal migration of the stent was observed. Seven out of eight patients (88%) had their leakage resolved after stent therapy.Conclusions Insertion of fully covered SEMSs is an alternative tool for the treatment of esophageal leakage in children and preterm infants, and successful with only one single application in selected cases. It can be used either following previous therapy or as part of an emergency procedure. Because of the absence of manufactured, age-related devices SEMSs that are originally designed for other organs can be applied.
Keywords: leakage; perforation; esophagus; stenting; endoscopy; children